Recurrent pulmonary arteriovenous malformation in a patient with Sjögren syndrome: A case report. Issue 41 (14th October 2022) - Shin, Yoon Mi; Kim, Yook; Yang, Jiyoul; Yang, Bumhee; Choi, In Ah; Lee, Ki Man
Abstract : Rationale: Pulmonary manifestations of Sjögren syndrome (SS) are variable and may involve the airway or lung parenchyma and increase the risk of vascular and malignant disease. However, to date, only one case of pulmonary arteriovenous malformation (AVM) has been reported in a patient with SS. Here, we report a rare case of recurrent pulmonary AVMs with aggravating multiple cysts in a patient with SS during a period of 14 years. Patient concerns: A 45-year-old woman was diagnosed with SS and pulmonary AVM in the right lung. Her AVMs were embolized successfully and she was followed up annually for 14 years. Eleven years after the initial treatment, her chest computed tomography showed new pulmonary AVMs in the left lung with aggravating multiple cysts. Diagnosis: We diagnosed her with SS according to the American–European consensus group criteria of 2010. Chest computed tomography and angiographic findings confirmed the recurrence of pulmonary AVMs. Interventions: The patient's recurrent pulmonary AVMs were successfully treated by embolization. Outcomes: Although her multiple cystic lung lesions had been aggravating during 14 years, she received embolization for the pulmonary AVMs twice and developed no complication related to these procedures. Currently, the patient is 56 years old and still alive with good performance state. Lessons: To date, only one case of pulmonary AVM has been reported in a patient with SS. The patient died 2.5 years after the diagnosis without recurrence of AVM. Here, we present a rare case of recurrent pulmonary AVMs associated with aggravating multiple cysts in both lungs, which were observed during long-term follow-up, in a patient with SS.